Pertaruhan Identitas dan Narasi: Virtual Community VS Real Community - Nuga, Valentinus Generosus (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2018)
This research focuses on studying the influence of technological advances of communication. Communication through social media networks has formed a platform for new communities which are called virtual communities. The presence of these virtual communities have “shifted” existing communities which were called organic communities or traditional communities or real communities. Researcher argues that in this era, Indonesians cannot avoid a new way of communicating. Convenience in connectedness and long-distance has helped people connect easily and efficiently. Elaboration which is conducted in this research is about the face of the world of communication today. The goal is to find an intrinsic value of communication in any community that emphasizes honesty and truth in the identity of communicators and communicants as well as shared narrative information. The researcher concludes that the model of communication in any community must be oriented to the truth and honesty of identity and narrative information.